Independent social work practices with adults in England: An appreciative inquiry of a pilot programme. (January 2017) - Teater, Barbra; Carpenter, John
Summary: Social Work Practice Pilots with adults was a government initiative in England (2011–2014) that created seven social work practices independent from local authorities/government. The stated aims were to reduce bureaucracy, promote professional discretion and expertise, and reduce the size of the public sector. The Social Work Practice Pilots were social work-led and comprised between five and 100 social workers and/or other professionals/non-professionals. This article describes how the methodology of appreciative inquiry was used to investigate how the Social Work Practice Pilots in England were developing as independent practices. Information was obtained through two, two-day site visits at each Social Work Practice Pilot, and two shared learning workshops with representatives from the Social Work Practice Pilots. Findings: Social Work Practice Pilots were found to be developing in accord with the following four key aims of the pilots: (1) spend more time with clients (service users), (2) a more responsive service, (3) more control over the day-to-day management, and (4) think creatively about resource use. Social Work Practice Pilots reported a reduction in bureaucracy and an ability to create flexible practices that more appropriately met the needs of the communities. Applications: The findings provide an initial indication of how social work practice could develop independently of local authorities and suggest possible benefits to staff and clients. The study demonstrated how the AI approach to research and consultancy can serve as a participative learning process when exploring social work practice. The strengths and limitations of the approach are discussed.